2022
DOI: 10.1158/1078-0432.ccr-22-2576
|View full text |Cite
|
Sign up to set email alerts
|

hENT1 Expression Predicts Response to Gemcitabine and Nab-Paclitaxel in Advanced Pancreatic Ductal Adenocarcinoma

Abstract: Purpose:Modified FOLFIRINOX (mFFX) and gemcitabine nab-paclitaxel (GnP) remain standard first line options for patients with advanced pancreatic ductal adenocarcinoma (PDAC). Human equilibrative nucleoside transporter 1 (hENT1) was hypothesized to be a biomarker of gemcitabine in the adjuvant setting, with conflicting results. In this study, we explore hENT1 mRNA expression as a predictive biomarker in advanced PDAC. Experimental Design: COMPASS was a prospective observational trial of patients with advanced P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A recent study demonstrated that hENT1 , a gemcitabine-specific gene, was predictive of response to gemcitabine-nab-paclitaxel in the COMPASS trial, suggesting that GemPred will most likely also predict the response to the dual regimen. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that hENT1 , a gemcitabine-specific gene, was predictive of response to gemcitabine-nab-paclitaxel in the COMPASS trial, suggesting that GemPred will most likely also predict the response to the dual regimen. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Frequency of Maximal Toxicity Events recent study demonstrated that hENT1, a gemcitabinespecific gene, was predictive of response to gemcitabinenab-paclitaxel in the COMPASS trial, suggesting that GemPred will most likely also predict the response to the dual regimen. 31 We also tested the prognostic value of the GemPred1 status in patients treated who had postoperative adjuvant mFOL-FIRINOX and who received a gemcitabine-based chemotherapy after relapse. In this comparison, the GemPred1 status obtained on a chemotherapy-naive sample was not predictive of postrelapse CSS for patients retreated using gemcitabine-based therapy after mFOLFIRINOX failure.…”
Section: Gempred+ Mffxmentioning
confidence: 99%
“…Most clinical studies including systematic reviews and meta-analyses reached the conclusion that high hENT1 expression is predictive of gemcitabine sensitivity in the systematic chemotherapy of PDACpatients [ 30 34 ]. Especially in adjuvant chemotherapy, a number of studies already reported the hENT1 is a strong independent prognostic factor in PDAC patients who receive gemcitabine-based chemotherapy after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that patients with APC with a low SAA may be preferentially treated with mFOLFIRINOX. Previous studies have found that the high expression of human Equilibrative Nucleoside Transporter 1 (hENT1) is related to longer OS in patients with APC received AG, 33 while Hepatocyte Nuclear Factor-1A (HNF1A) positive patients might benefit from FOLFIRINOX. 34 In contrast to these studies, SAA can be obtained from serum as a routine clinical biochemical test, which is more convenient, safer and economical.…”
Section: Discussionmentioning
confidence: 99%